Choroidal changes in human myopia: insights from optical coherence tomography imaging. (19th December 2018) - Read, Scott A; Fuss, James A; Vincent, Stephen J; Collins, Michael J; Alonso‐Caneiro, David
Abstract : The choroid is a vascular tissue which plays a range of critical roles in the normal physiology of the eye, such as supplying the outer retina with oxygen and nutrients and the regulation of intraocular pressure. There is also substantial evidence, particularly from animal studies, that the choroid plays an important role in the regulation of eye growth and the development of common refractive errors like myopia. In recent years, advances in optical coherence tomography technology have improved our ability to image and measure the choroid in the human eye. Research using this technology over the past decade has dramatically improved our knowledge of the normal choroid, and its potential role in the regulation of eye growth and refractive error development. This review aims to provide an overview of recent work examining the normal human choroid, its changes with myopia and the possible role of the choroid in the mechanism regulating eye growth. Studies have demonstrated that choroidal thinning accompanies the development and progression of myopia, and have established a close link between eye growth and choroidal thickness changes. Dramatic thinning of the choroid is seen with high myopia, and associations are also observed between choroidal thinning and reduced vision, and the development of retinal pathology associated with high myopia. In the short‐term, environmental factors known to be associated with myopia development and more rapid eye growth typically lead to a thinning of the choroid, whereas factors linked to a slowing of eye growth are typically associated with short‐term choroidal thickening. Collectively, these findings suggest that the choroid is an important biomarker of eye growth in the human eye, and additional research to better understand the human choroid is likely to further our knowledge of the signals and pathways regulating eye growth, myopia development and progression.